ONE TO MANY SUB-FLOW REALIZATION IN BUSINESS PROCESSES - Abubakirova, A.; Shalkharbay-uly, A. (Journal of Emerging Technologies and Computing, 2020)
The present paper aims to call into question how realize complex type by using BPM and C# coding to connect from one to many processes. In the background describes the IT concept part as a table and questions for monitoring all cases of Event process in SDU, data saving in one process, correction of responsible approvers. The using BPM methods implement in business processes: description and design, development and implementation, monitoring and control, optimization without different changes by table or figures. Complex Event Processing (CEP) techniques can detect event patterns that are specified as CEP rules. In the process of this article, process maturity was important, such as characteristics and abilities that determine the current state of the company on the path to understanding and managing processes. Techniques and method results will be shown by realization possibility and using comfortability with the eBA workflow system.